Technological Capital and its Impact on the Level of Innovation Maturity in IT Enterprises: A Quantitative Research in Lubusz Voivodeship in Poland - Monika INKÓW (Communications of International Proceedings, 2025)
In the current turbulent economic environment, innovation is considered a factor ensuring the survival of enterprises. Introducing individual innovations is insufficient; innovations should be developed continuously, and enterprises should improve their innovation activities to achieve subsequent levels of innovation maturity. To achieve this, it is crucial to identify the factors that determine innovation. It turns out that technological capital is one such determinant. The aim of this study was to examine the relationship between an organization's technological capital and the level of innovation maturity it has achieved. The research data was collected using two methods: individual interviews, which were supplemented in the second stage with a survey. Seventy IT entities in the Lubusz Voivodeship, Poland, participated in the study. The study results confirmed the existence of a positive, relatively strong relationship between the technological capital of the surveyed enterprises and their level of innovation maturity. The study results show that enterprises should take care of the development of the technological capital of the organization, because it can contribute to achieving a higher level of innovation maturity and thus achieving excellence in innovation activities, and thus achieving competitive advantages.
Keywords: technological capital; innovation; innovation maturity.